Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Berbantuan Media Infografis pada Materi Membaca Cepat untuk Meningkatkan Hasil Belajar AKM Literasi Siswa Kelas V - Az Zahra, Salsabila; Purwati, Panca Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
To increase student enthusiasm and learning outcomes, learning is needed that applies innovative and creative learning models and media. One learning model that can be used is the Jigsaw type cooperative learning model with infographic media. The purpose of this research is to determine the effectiveness of implementing the Jigsaw learning model assisted by infographic media in speed reading (scanning) material in an effort to improve student learning outcomes in literacy AKM. This research uses a qualitative descriptive research method. Data collection instruments were carried out using observations and tests. Based on research results, the application of the Jigsaw learning model assisted by infographic media on speed reading (scanning) material was able to improve learning outcomes with learning outcomes in cycle I reaching 67 with a percentage of 33.3% of which 30 students only completed 10. Meanwhile, learning outcomes in cycle II reached 76.67 and the percentage of students who completed was 66.6%, where of the 30 students, 20 students had passed.